PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN, TRAINING DAN KEMAMPUAN MANAJEMEN TERHADAP KEUNGGULAN BERSAING - Mince Batara; Rati Pundissing; Linda Uddu (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of Market Orientation, Entrepreneurial Orientation, Training, and Management Ability on Competitive Advantage in Bakti culinary businesses. This research is a quantitative study with a questionnaire data collection method. The number of samples was 17 respondents. The analysis technique uses Multiple Linear Regression Analysis with the assistance of SPSS. The results of this study indicate that Entrepreneurial Orientation, Training, Management Capability, and Market Orientation simultaneously have a positive effect on competitive advantage. The suggestion for the next research is to discuss deeper into the comparison of management capabilities in terms of soft skills obtained self-taught with training, so that it can contribute to competitive advantage. Keywords: Competitive Advantage; Entrepreneurship Orientation; Training; Market Orientation; Management Capability